HERMENEUTIC MODEL OF TRANSLATION OF TEXTS FROM OIL AND GAS SPHERE - Yanyshyn О. К. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
Scientific and technical translation in the sphere of oil and gas is full of challenges concerning terminology, metaphorical lexicon, and grammar constructions. It is argued that understanding is a base for translating, moreover, translation adequacy is a chief criterion for the translation quality. Hence, hermeneutics, as a science of comprehension and interpretation of texts, could be rightly regarded as the methodological and intellectual foundation for the translation adequacy. In the article, a suggested hermeneutic four-level model concerning translation analysis of the texts from gas and oil sphere is described.